2001
DOI: 10.1152/ajplung.2001.281.1.l193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic hypoxia on agonist-induced tone and calcium signaling in rat pulmonary artery

Abstract: The effect of chronic hypoxia (CH) for 14 days on Ca2+ signaling and contraction induced by agonists in the rat main pulmonary artery (MPA) was investigated. In MPA myocytes obtained from control (normoxic) rats, endothelin (ET)-1, angiotensin II (ANG II), and ATP induced oscillations in intracellular Ca2+ concentration ([Ca2+]i) in 85-90% of cells, whereas they disappeared in myocytes from chronically hypoxic rats together with a decrease in the percentage of responding cells. However, both the amount of mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 46 publications
(78 reference statements)
5
54
0
Order By: Relevance
“…Notably, a recent study demonstrated that the alterations in the protein expression profile after allergen sensitisation and challenge partly correlated with those observed in hypoxia [33], which is known to induce PAH and increased vascular responses to vasoconstrictors [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study demonstrated that the alterations in the protein expression profile after allergen sensitisation and challenge partly correlated with those observed in hypoxia [33], which is known to induce PAH and increased vascular responses to vasoconstrictors [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…A cumulative concentration-response curve to sildenafil (0.1 nM-1 M) was then constructed on PE-precontracted PA rings. Because reactivity to agonists is reduced in main PA rings from CH rats (4,5,40), 0.3 and 3 M PE were used to obtain the same value of precontraction in rings from control and CH rats, respectively. Some experiments were also performed in endothelium-denuded rings.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the down-regulation of Kv1.5 will lead to PASMC depolarization and opening of L-type Ca 2ϩ channels and will sustain the increase in [Ca 2ϩ ] i and thus NFAT activation. The increase in PASMC [Ca 2ϩ ] i might also be promoted by other possibly primary PASMC abnormalities, like the dys-regulated serotonin transporter, up-regulation of TRP channels (37), or decreased SERCA activity (38). Activation of NFAT will complete a reinforcing positive-feedback loop with the down-regulation of Kv1.5 and may explain why the phenotype is preserved in PASMC in culture, in the absence of endothelium-derived or circulating factors.…”
Section: Mitochondria and Pahmentioning
confidence: 99%